The Impact of the Convention on the Elimination of All Forms of Discrimination Against Women in Select African States. (19th June 2019) - Banda, Fareda
Abstract: While the United Nations Convention on the Elimination of all Forms of Discrimination against Women (CEDAW) is seen to be an African success story, in order to obtain some sense of the impact of CEDAW in African legal systems, this article considers cases in which CEDAW provisions on the family have been invoked in those jurisdictions and provides a snapshot of key issues identified by the Committee in the case law, including changes in Constitutions. This set in the context of the challenges of applying international standards to local contexts.